How Mixed Performance Feedback Shapes Exploration: The Moderating Role of Self-Enhancement - Lauenstein, Franziska; Newark, Daniel A.; Baumann, Oliver (Organization Science, 2025)
We conduct an experiment to examine how providing decision makers with high versus low peer performance information influences choices between exploration and exploitation. Previous work on organization-level learning suggests that a high-performing peer would fuel exploration, whereas a low-performing peer would dampen it. In line with this, we find that individuals who receive information about a high-performing peer explore more than those who receive information about a low-performing peer. However, we also find that compared to individuals with a low tendency to self-enhance, individuals with a high tendency to self-enhance are less likely to explore when receiving information about a high-performing peer. In fact, these individuals explore at levels comparable to those who receive information about a low-performing peer. We explain this behavioral pattern by demonstrating that as individuals learn and improve, information about a high-performing peer increasingly results in mixed performance feedback; under these conditions of relative interpretive flexibility, exploration is moderated by decision makers’ tendency to self-enhance. When these individual dynamics are aggregated, our data suggest that an organization that provides peer performance information may experience either the same or less exploration than an organization that does not, with the exact difference depending on its proportion of high self-enhancers. These insights into the contingencies and aggregate effects of how individuals interpret and respond to peer performance information are particularly relevant given recent interest in designing organizations that shape employee behavior through the provision of feedback rather than through traditional instruments of coordination and control, such as incentives or hierarchy. Funding: This work was supported by Danmarks Frie Forskningsfond [Grant 25194]. Additionally, this research was supported by a grant from the HEC Paris Foundation.